Design and Implementation of Iraqi Virtual Library - Kazem, Bahaa I.; Abdulla, Mohammed Najm; Raouf, Jalal B.; Colin, Jean- Noël; Levine, Barry (Al-Khwarizmi Engineering Journal, 2010)
In developing countries, individual students and researchers are not able to afford the high price of the subscription to the international publishers, like JSTOR, ELSEVIER,…; therefore the governments and/or universities of those countries aim to purchase one global subscription to the international publishers to provide their educational resources at a cheaper price, or even freely, to all students and researchers of those institutions. For realizing this concept, we must build a system that sits between the publishers and the users (students or researchers) and act as a gatekeeper and a director of information: this system must register its users and must have an adequate security to ensure that only the affiliated students are able to access its services.  It also needs to have security and trust mechanisms built-in for commercial partners to accept their connections. This paper describes the work done on the design and implementation of the IVL (Iraqi Virtual Library).